Transforming growth factor-β1 protects mechanically injured cortical murine neurons by reducing trauma-induced autophagy and apoptosis - Li, Yanlei; Deng, Huixiong; Zhang, Hengyao; Yang, Lin; Wang, Shenmiao; Wang, Haoyang; Zhu, Jiacheng; Li, Xiaoning; Chen, Xiaoxuan; Lin, Yinhong; Li, Rui; Wang, Gefei; et al. (Frontiers in Cellular Neuroscience, 2024)
Transforming growth factor β1 (TGF-β1) has a neuroprotective function in traumatic brain injury (TBI) through its anti-inflammatory and immunomodulatory properties. However, the precise mechanisms underlying the neuroprotective actions of TGF-β1 on the cortex require further investigation. In this study, we were aimed to investigate the regulatory function of TGF-β1 on neuronal autophagy and apoptosis using an in vitro primary cortical neuron trauma-injury model. LDH activity was assayed to measure cell viability, and intracellular [Ca 2+ ] was measured using Fluo-4-AM in an in vitro primary cortical neuron trauma-injury model. RNA-sequencing (RNAseq), immunofluorescent staining, transmission electron microscopy (TEM), western blot and CTSD activity detection were employed. We observed significant enrichment of DEGs related to autophagy, apoptosis, and the lysosome pathway in trauma-injured cortical neurons. TEM confirmed the presence of autophagosomes as well as autophagolysosomes. Western blot revealed upregulation of autophagy-related protein light chain 3 (LC3-Ⅱ/LC3-Ⅰ), sequestosome 1 (SQSTM1/p62), along with apoptosis-related protein cleaved-caspase 3 in trauma-injured primary cortical neurons. Furthermore, trauma-injured cortical neurons showed an upregulation of lysosomal marker protein (LAMP1) and lysosomal enzyme mature cathepsin D (mCTSD), but a decrease in the activity of CTSD enzyme. These results indicated that apoptosis was up-regulated in trauma-injured cortical neurons at 24 hours, accompanied by lysosomal dysfunction and impaired autophagic flux. Notably, TGF-β1 significantly reversed these changes. Our results suggested that TGF-β1 exerted neuroprotective effects on trauma-injured cortical neurons by reducing lysosomal dysfunction, decreasing the accumulation of autophagosomes and autophagolysosomes, and enhancing autophagic flux.